Application of the program to improve the autonomy of pre-school children - Samamé Gonzáles, Angela María Teresa (2021)
The objective of the research carried out was to demonstrate that the application of the “Application of the program to improve the autonomy of pre-school children” Program influenced the autonomy of 24-month-old children in a Pronoei in the San Juan de Miraflores district (Lima, Peru). The research approach was quantitative, applied or practical, the design was quasi-experimental and the method corresponded to the hypothetical deductive one. The study population was 64 students. The instrument was a checklist that was structured in three dimensions, such as affective security, freedom of movement, appropriate spaces and materials. The program lasted twelve weeks, for which the parents actively participated before, during and after each class session. The results showed that the program had a positive influence on the autonomy of the children, which was demonstrated with the application of the U Mann Whitney test, because the level of significance calculated in the pre-test was 0.052, and in the post-test it was registered .000, a similar situation occurred in the dimensions. Finally, it is concluded that the application of the program improves and reinforces the autonomy of children, which is why it should be replicated in other groups.